Executive directors remuneration, turnover and firm performance in fraud and lawsuit frims / Suria Majdi and Professor Dr Rashidah Abdul Rahman - Majdi, Suria; Abdul Rahman, Professor Dr Rashidah (2012)
The recent wave of corporate fraud has raised substantial concerns about the effectiveness of corporate governance in Malaysia. This study determines whether fraud firms reduce their executives' remuneration to improve the firm's performance and also to discipline the executive directors' behaviour so that they do not deviate from the shareholders' wealth maximizing policy. The sample of this study consists of 136 firms which comprise of 68 fraud firms that experienced fraud revelation over the periods of2001 to 2006 and 68 non-fraud firms. The results from the independent sample t-test analysis reveal that there is a significant difference in the median executives' remuneration between fraud and non-fraud firms in the second year after the fraud revelation. It is found that fraud firms reduced the executives' remuneration by 6% while non-fraud firms still increased the executives' remuneration by 8.08%. Further analysis shows in the fraud and lawsuit firms' turnover. we find that the new appointed executive may be paid at a lower rate compared to the other executive directors in non fraud and lawsuit firms.